Analysis of Learning Style and Learning Media on Early Childhood Counting Skills - Nurhikmah; Ibnu Imam Al Ayyubi; Firda Noerzanah; Eko Prayetno; Siti Fatinnah bin Abd Rahman (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
This study aims to identify the influence of learning styles (kinesthetic, visual, and auditory) and gender on early childhood counting skills at Inpres Mannurukki Kindergarten, TKIT At-Tibyan, and Bone Kindergarten. The research method used was quantitative with an experimental design. The sample consisted of 45 students, with 17 male students and 28 female students, who were divided based on the learning styles applied. Data were collected through measurement of children's counting skills and analysed using descriptive statistical test, normality test, Levene test, and Two-Way ANOVA test. The results of the descriptive analysis showed that the mean scores of the counting skills of male and female students varied depending on the learning style applied. Kinesthetic learning style gives good results for students who are actively moving, visual learning style is more effective with the use of digital media, and auditory learning style shows good results with the use of songs and rhythms. The Two-Way ANOVA test showed that there was no significant difference between learning styles on children's numeracy skills, but there was a significant difference between gender and the interaction between learning styles and gender. Boys excel in auditory and kinesthetic learning styles, while girls excel in visual learning styles. This study concludes that learning that is tailored to learning styles and gender characteristics can improve early childhood numeracy comprehension. The implication of this research is the need for a differentiated learning approach according to children's needs to maximise learning outcomes.